2015
DOI: 10.1007/s00232-015-9844-3
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of the Selected Metal Ions in Saccharomyces cerevisiae Cells Under Treatment of the Culture with Pulsed Electric Field (PEF)

Abstract: The obtained results demonstrated an influence of PEF on increase in accumulation of various ions in S. cerevisiae cells. Optimization of particular PEF parameters and ions concentrations in the medium caused twofold increase in accumulation of magnesium and zinc ions and 3.5-fold higher accumulation of calcium ions in the cells. In the case of ion couple, accumulation of magnesium and zinc was, respectively, 1.5-fold and twofold higher in comparison to the control cultures. Yeast cells biomass enriched with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…To prevent these adverse changes, the microencapsulation process is used [10]. One of the encapsulation methods is the accumulation of minerals in the yeast cells of S. cerevisiae [11][12][13][14]. In the study of Kyyaly et al [15] it was demonstrated that feeding anemic rats with iron-enriched yeast is more efficient than inorganic treatment in recovery from iron deficiency.…”
Section: Of 19mentioning
confidence: 99%
“…To prevent these adverse changes, the microencapsulation process is used [10]. One of the encapsulation methods is the accumulation of minerals in the yeast cells of S. cerevisiae [11][12][13][14]. In the study of Kyyaly et al [15] it was demonstrated that feeding anemic rats with iron-enriched yeast is more efficient than inorganic treatment in recovery from iron deficiency.…”
Section: Of 19mentioning
confidence: 99%
“…Prevention or treatment of iron deficiency can be achieved by enriching microorganisms (for example, yeast) used in the food industry with iron ions through the application of pulsed electric field (PEF) [ 8 ]. Previous studies have shown that using this technique increases the efficiency of ion accumulation by yeast from the medium [ 9 , 10 , 11 , 12 , 13 , 14 ]. Higher ion accumulation in cells results from the increased permeability of the cell membrane due to the phenomenon of electroporation.…”
Section: Introductionmentioning
confidence: 99%
“…Employing living microorganisms for metal biosorption has an advantage of simultaneously exploiting their inherent ability of absorbing and accumulating heavy metals intracellularly, a process known as bioaccumulation (Pankiewicz et al, 2015). Recently, a system of continuous growth of S. cerevisiae was demonstrated to be an efficient method of removing copper and lead ions from water (Amirnia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%